2004
DOI: 10.1080/17461390400074203
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of perceived health and appearance improvement, and self‐motivation, with adherence to exercise in previously sedentary women

Abstract: Previously sedentary women in the southeast United States (M age = 35.9 years, SD = 10.1), whose primary reason for beginning an exercise program was either health improvement (N = 48) or appearance improvement (N = 42), were assessed to estimate relationships between perceived progress on these factors, self-motivation, and exercise program attendance. Non-significant bivariate correlations were found between attendance and changes in measures of perceived health (r = -.24) and appearance (r = -.02), over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…To minimise impact of advancing age on the body composition we recommend that obese women over 30 years of age walk at least 10,000 steps per day and obese women over 45 years of age at least 12,500 steps per day (23)(24)(25). King et al (26), Ross and Janiszewski (27) and Annesi (28) showed that PA can bring health benefits without changes in anthropometric indicators and thus reduces the risk of complications of obesity, improves psychological well-being and also leads to better adherence to the reduction regime. The exercise alone does not always result in significant weight reduction, but has a number of positive effects relating to, inter alia, improvement of physical condition and thus positively affecting health.…”
Section: Discussionmentioning
confidence: 99%
“…To minimise impact of advancing age on the body composition we recommend that obese women over 30 years of age walk at least 10,000 steps per day and obese women over 45 years of age at least 12,500 steps per day (23)(24)(25). King et al (26), Ross and Janiszewski (27) and Annesi (28) showed that PA can bring health benefits without changes in anthropometric indicators and thus reduces the risk of complications of obesity, improves psychological well-being and also leads to better adherence to the reduction regime. The exercise alone does not always result in significant weight reduction, but has a number of positive effects relating to, inter alia, improvement of physical condition and thus positively affecting health.…”
Section: Discussionmentioning
confidence: 99%
“…Regular and adequate training since childhood should not only lead to the development of fitness and motor performance, but also to the development of a series of personal traits of the individual (Kahlin et al, 2016;Joyner & Loprinzi, 2018). Many of those personal traits are considered to be the predictor for adherence to physical activity (Annesi, 2004). These traits include: the ability to exert effort, determination, diligence, inclination to continue in the activity and to fulfil the task (Annesi, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…From this point of view, individual satisfaction with reaching relevant goals leading to regular exercising played a signifi cant role in the results of the women involved in the program. On the other hand, especially external motivation oriented to body image and mass-media supported ideals can lead to involvement in physical activity and exercise programs, but this involvement will probably not be persistent, especially in middle aged women (Annesi, 2004;Biddle & Mutrie, 1991;Ryan et al, 1997). Thus, unrealistic expectations can become demotivating (Roberts, 2001).…”
Section: Figmentioning
confidence: 99%
“…a theory accenting the setting and defi nition of goals, estimates of progress and planning, increases in resistance and stamina (Annesi, 2004). Bandura's social-cognitive theory (Bandura, 2001) emphasizes self effi cacy and the awaited result in fulfi lling set aims.…”
Section: Introductionmentioning
confidence: 99%